Electrocardiographic phenotype of exercise-induced arrhythmogenic cardiomyopathy: A retrospective observational study - Miljoen, Hielko; Spera, Francesco; Van Kolen, Katrien; Saenen, Johan; Claessen, Guido; Huybrechts, Wim; Sarkozy, Andrea; Heidbuchel, Hein (Frontiers in Cardiovascular Medicine, 2022)
Introduction The right ventricle can be susceptible to pathologic alterations with exercise. This can cause changes to the ECG. Our aim was to identify the electrocardiographic phenotype of exercise induced (ExI) arrhythmogenic cardiomyopathy (ACM). Methods A retrospective analysis of ECGs at rest, peak exercise and 1 min of recovery in four groups of individuals was performed: Arrhythmogenic Cardiomyopathy with genetic confirmation (Gen-ACM; n = 16), (genetically negative) ExI-ACM (n = 15), control endurance athletes (End; n = 16) and sedentary individuals (Sed; n = 16). The occurrence of ventricular arrhythmias (VA) and, at each stage, QRS duration, Terminal Activation Delay (TAD), the ratio of the sum of the QRS durations in the right precordials (V1-V3) over that in the left precordials (V4-V6; R/L duration ratio), the presence of complete RBBB and T-wave inversion (TWI) beyond lead V2 were evaluated. Results At rest, complete RBBB was exclusively found in Gen-ACM (6%) and ExI-ACM (13%). No epsilon waves were identified. TWI beyond V2 was uniquely present in Gen-ACM (73%) and ExI-ACM (38%; p < 0.001). VA was present in Gen-ACM (88%); ExI-ACM (80%), End (25%) and Sed (19%; p < 0.001). The presence of R/L duration ratio of >1.2 and TAD ≥ 55 ms were not significantly different over the four groups (p = 0.584 and p = 0.218, respectively). At peak exercise the most striking finding was a significant decrease of the R/L duration ratio in individuals with ACM, which was the result of lateral precordial QRS prolongation. Conclusion ExI-ACM shares important ECG-features with Gen-ACM, suggesting a similar underlying pathogenesis regardless of the presence or absence of desmosomal mutations.